Individual Coaching on Self-Efficacy, Control and Medication Adherence in Patients with Tuberculosis - Sukartini, Tintin; Pratiwi, IkaNur; Koa, Maria Fatima (International Journal of Psychosocial Rehabilitation, 2020)
Self-efficacy, infection prevention behavior and the treatment adherence are the 3 factors that support TB control programs. The purpose of this study was to analyze the effect of individual coaching on improving self-efficacy, infection prevention behavior, and adherence to the TB treatment. This study used a quasi-experiment with a pre-posttest control group design. The sampling technique used was total sampling. Sixty respondents were divided into control and treatment groups. Each group had 30 respondents. Individual coaching was carried out at the Oesapa Health Center divided into 5 stages with a 60-minute home visit. The respondents were given questionnaires and then observed. The study was conducted for 2 weeks. The independent variable in this study was individual coaching and the dependent variables were self-efficacy, infection prevention behavior and the treatment adherence of tuberculosis patients. The Wilcoxon sign rank test and the Mann-Whitney test were used for statistical analysis. The statistical tests showed that individual coaching has an effect on self-efficacy (p=0.000), on the knowledge of infection prevention behavior (p=0.000), attitudes (p=0.000) and on actions (p=0.000) and the adherence to the tuberculosis treatment (p=0.000). The individual coaching method affects self-efficacy, the prevention of infection behavior and the adherence to TB treatment as well as the suppression of infection and dropping out of the TB treatment.